COVID-19 Pandemic: Impacts, Craftsmen’s Living Strategies, and Economic Recovery of Bamboo Handicraft Enterprise in Gunungkidul, Indonesia - Utomo, Marcellinus; Sudomo, Aris; Pieter, Levina Augusta Geraldine; Maharani, Dewi; Swestiani, Dila; Siagian, Carmen Minerva; Fambayun, Rizki Ary; Perdana, Aulia; Roshetko, James Michael (Forest and Society, 2022)
The COVID-19 pandemic has affected the household bamboo handicraft industry in rural areas. A comprehensive study was conducted to identify impacts, living strategies, and economic recovery; the findings will be used as a basis to recommend supporting policy to create a more resilient bamboo handicraft business. This study applied phenomenological approach to interpret the social impacts of the COVID-19 pandemic. In December 2021, 30 bamboo craftsmen in Semin Village, Gunungkidul, Yogyakarta Special Province were interviewed. Results show that 96.7% of bamboo craftsmen experienced a decrease in profit, with 46.6% reporting no order for a long period. The profit earned by craftsmen decreased by 76.50%. Bamboo craftsmen adapted to the COVID-19 pandemic by minimizing capital expenses, creating innovations marketing in options (i.e., direct sales, selling online) and focusing on alternative income sources (farming, hunting and gathering, selling food, and becoming laborers) to survive. As the spread of the virus was controlled, leading to the relaxation of restrictions on economic activities, the bamboo industry in Semin has entered an economic recovery phase. Currently, the average profit has reached 66.18%, compared to the profit earned in normal pre-pandemic situation. We believe the government should facilitate craftsmen to build their capacity in e-commerce, export mechanism, market network creation, tool acquisition, and English proficiency. This would enhance the bamboo handicraft industry in Semin to be more resilient facing future challenges